Assessment of oral mucositis degree due to cytostatic treatment in patients with malignant lymphomas - Muica Adrian; Berneanu Florentin-Daniel; Hănțoiu Liana; Kinga Dorner; Crăciun Adriana-Elena ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2019)
Introduction: Oral mucositis characterized by inflammation of the oral mucosa, ulcers, angular cheilitis, accompanied by pain in the maxillary facial area are symptoms of patients who have undergone cytostatic treatment, affecting over 75% of high-risk patients.